COMPARISON OF CALCULATING OPERATIONS PERFORMANCES ON DATABASE SERVER AND WEB SERVER. - AYIK, Yusuf Ziya; KAHVECİ, Ferhat (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2019)
Many computer systems are combined to provide a service to users. Each system has specific tasks as part of the whole system. While some calculation operations can be processed on any server, some of them need a specific system platform to run. For the calculating operations which can be processed on any server, the main criteria will be related to the performance. If we have detailed information about the calculating performance of systems, we may set the calculating operations on the appropriate system. The aim of this study is the comparison of calculating operation on the database server and web server. Bubble sort and pi number algorithm were selected for the calculating operation. These algorithms' runtime results are obtained both by a database server and a web server. Algorithm functions with the same flow processes have been used for both server systems. The variables are predefined to prevent data transfer delay in systems. Thus, the performance results are focused on calculating performances on the servers. The results show, there is an appreciable difference between database and web server in terms of calculation time. The web server was the more performant than the database server, and the implementation of algorithms was simpler in the web server.